Geomorphological study of Alsonawber basin using geographic information systems - Eyed, Safea; Kadora, Aisha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to obtain the most important geomorphological characteristics for Alsonawber basin using applied geographic information system techniques based on digital elevation model DEM. Like determining slope types, slope degrees, aspect, hill shade, hydrological basin network, define the surface hydrology, and making spatial analyst and 3d analyst using geographic information system.